Mulheres na política: uma análise do instrumento inclusivo brasileiro - Dias, Bianca Vasconcelos Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This essay starts with the low representative of females on the elective charges, in the Brazilian politic, to question the mechanisms that serves to reaffirm that positions. Taking this scenario, is discussed the need to apply laws that bring more women to the politic, focus on the low chamber. To understand this situation it is analyzed the law number 9504/96 that implies a reservation of 30% of female application to the parties, there are listed the changes that this law has been trough and the impact that this has made in the females applications and in the number of women that wore elected to the lower chambers. To bring the context that Brazil is implied will be analyzed the latin American countries too

O presente trabalho parte da baixa representatividade feminina nos cargos eletivos, dentro da política brasileira, para questionar os mecanismos que servem para reafirmar tal posição. Traçado esse cenário, se discute a necessidade de aplicações de leis que tragam maior presença feminina dentro da política, com foco na Câmara de Deputados. Para entender essa situação analisa-se a Lei 9504/96 que determina a reserva de 30% das candidaturas dos partidos para mulheres, são elencadas as mudanças que esse artigo teve até recentemente e o impacto que isso levou tanto nas candidaturas femininas quanto no número de mulheres eleitas para a Câmara de Deputados. Para se contextualizar o Brasil traça-se um breve panorama dessa situação na América Latina
Keywords: Mulheres na politica; Igualdade; Igualdade perante a lei; Programas de ação afirmativa; Equality